1994
DOI: 10.1080/10610279408029869
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sensing based on membrane potential change induced by host-guest complexation at a membrane surface1

Abstract: 1994) Chemical sensing based on membrane potential change induced by host-guest complexation at a membrane surface 1 , Supramolecular Chemistry, 4:2, 101-113,Three new principles for discrimination of organic guests by the membrane potential change are described, which are based on the host-guest recognition of charged groups, hydrogen bonding groups, or steric shapes of nonpolar moieties. (i) Potentiometric discrimination by the recognition of charged groups has been attained by liquid membrane type electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
(7 reference statements)
6
20
0
Order By: Relevance
“…This result explains why PVC liquid membranes based on macrocyclic pentaamine show strong responses to anionic analytes without added anionic sites. [14][15][16] The site concentration dependence of the EMF responses calculated from the diffuse double layer-based model was well fitted to the observed one with the same stability constant of the protonated pentaamine-anionic analyte complex for membranes with various concentrations of anionic sites. This result allows us to explain the influence of the anionic site concentrations on the EMF response of macrocyclic pentaamine-based membranes as follows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result explains why PVC liquid membranes based on macrocyclic pentaamine show strong responses to anionic analytes without added anionic sites. [14][15][16] The site concentration dependence of the EMF responses calculated from the diffuse double layer-based model was well fitted to the observed one with the same stability constant of the protonated pentaamine-anionic analyte complex for membranes with various concentrations of anionic sites. This result allows us to explain the influence of the anionic site concentrations on the EMF response of macrocyclic pentaamine-based membranes as follows.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(vinyl chloride) (PVC), bis(2-ethyl-hexyl)phthalate (DOP), maleic acid, phosphate disodium salt, ortho phosphoric acid, tetrahydrofuran (THF) and potassium tetrakis(pchlorophenyl)borate (KTClPB) were purchased from Wako Pure Chemicals (Osaka, Japan). A lipophilic derivative of macrocyclic pentaamine (C16H33- [16]aneN5) [1] was synthesized according to a previously reported procedure. [16][17][18] Membrane preparation and EMF measurements Solvent polymeric membranes containing 1.5 wt% lipophilic macrocyclic pentaamine [1], 73.5 wt% plasticizer (DOP), 25 wt% PVC and anionic salt (KTpClPB) at the concentration versus to ionophore: 1 mol%, 10 mol% and 100 mol%, were prepared as follows: A homogeneous solution of lipophilic macrocyclic pentaamine, KTpClPB, DOP and PVC in THF (distilled from KOH prior to use) was poured into a glass ring (0.8-cm diameter) standing on a glass plate; the solvent was allowed to evaporate for 48 h. The thus-prepared membrane was mounted on a glass tube by Teflon tape.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for this latter hypothesis comes from proton binding studies of a pyridine-strapped 5,12-dioxocyclam-based macrocycle [47]. Meyer et al showed that this elaborated pyridinecontaining receptor behaves as a diprotic base with pK B1 =8.94(1) and pK B2 =2.32 (9). However, in this latter instance the diprotonated species was thought to be stabilized by additional intramolecular hydrogen bonding within the cavity.…”
Section: Ph Effectsmentioning
confidence: 99%
“…ISEs are also of obvious interest because they can help translate the chemistry of new substrate binding systems into tools that can be used to recognize selectively various targeted species in the presence of potentially interfering analytes. In the specific case of anion recognition, this approach has been explored extensively by Umezawa, Meyerhoff, Simon, Reinhoudt, Schmidtchen and others using a range of receptors including bis-guanidinium [1][2], porphyrins [3], protonated polyamines [4][5][6][7], and protonated sapphyrins [8][9][10], as well as a variety of Lewis acidic systems such as calixarenes [11][12][13][14][15], uranylsalenophenes [16][17], metalloporphyrins [18][19][20][21][22], metallocenes [23], other organometallic derivatives [24][25][26], and fluorinated compounds [27].…”
Section: Introductionmentioning
confidence: 99%